Prevalence Of Non-Specific Neck Pain Among Beautician’s. - Avatade, Vaishnavi Mohan; S. Rayjade , Amrutkuvar (Journal of Neonatal Surgery, 2025)
Background: Non-specific neck pain (NSNP) is a prevalent occupational health concern among beauticians due to prolonged static postures, repetitive movements, and ergonomic challenges. This study aims to determine the prevalence and severity of NSNP among beauticians and assess its impact on daily activities. non-specific neck pain (NSNP) is a common musculoskeletal disorder affecting individuals in various occupations, particularly those requiring prolonged static postures and repetitive movements. Beauticians are at a higher risk due to their work-related ergonomics, including prolonged neck flexion, repetitive hand movements, and static postures. Methodology: A total of 97 beauticians participated in this cross-sectional study. Data were collected using a structured questionnaire, including the Neck Disability Index (NDI) and Numeric Pain Rating Scale (NPRS). Descriptive statistics were used to analyze the prevalence and severity of NSNP. Results: Among the participants, 74.23% reported experiencing neck pain, while 25.77% had no symptoms. Based on the Neck Disability Index (NDI), 51.55% had moderate disability, 13.40% had severe disability, 9.28% had mild disability, and 25.77% reported no disability. The mean NDI score was 16.40 ± 9.03, indicating a moderate level of disability. The mean pain scores on the NPRS were 2.63 ± 1.64 at rest and 6.10 ± 2.28 during movement, with a statistically significant p-value (5.63 × 10⁻²⁸). The average age of participants was 31.19 ± 4.71 years, with a mean work experience of 6.34 ± 1.11 years. They worked an average of 6.14 ± 0.75 days per week and 6.96 ± 1.16 hours daily. Conclusion: The findings indicate a high prevalence of NSNP among beauticians, with a significant proportion experiencing moderate to severe disability. The results highlight the need for ergonomic interventions, postural awareness programs, and workplace modifications to reduce the burden of neck pain in this occupational group. Raising awareness about proper work practices and implementing preventive measures can help improve the musculoskeletal health of professionals in the beauty industry...